THE INFLUENCE OF PERCEIVED EASE OF USE, DISCOUNT, AND PERCEIVED USEFULNESS ON INTENTION TO USE GRAB APLICATION AND IT’s IMPACT ON PURCHASE DECISION OF GRAB SERVICES - Ritonga, Nursakinah; Astuti, Endang Siti; -, Sunarti (Accounting Department,, 2019)
The purpose of this study is to explain and analyze the influence of Perceived Ease of Use, Discount, Perceived Usefulness on Intention to Use the Grab application and its impact on Grab service purchasing decisions. This study uses a quantitative approach using explanatory research. The population of this study is undergraduate students in business administration study programs for 2017 and 2018 Faculty of Administrative Sciences, Universitas Brawijaya, Malang. with a total of 734 people. To determine the sample of the population, researchers used the Yakane formula to obtain the number of respondents as many as 90 people. The sampling technique of this study is non probability sampling technique with the number of samples taken proportionally following the number of students in 2017 and 2018. The method of data collection used a questionnaire distributed to the respondent classes and calculated using a Likert scale.Data analysis methods consist of test instruments, research requirements testing and hypothesis testing with path ananlysis by SPSS. The results of this study indicate that the Perceived Ease of Use, Discount, Perceived Usefulness has a positive and significant effect on the Intention to use Grab application. In addition the variable Perceived Ease of Use, Discount, Intention to Use Grab application also has a positive and significant influence on purchasing decisions. While the Perceived Usefulness variable has a positive but not significant effect on Purchasing Decisions.